Tubal ectopic pregnancy: our experience from 2000 to 2013 - Berretta, Roberto; Dall'Asta, Andrea; Merisio, Carla; Monica, Michela; Lori, Letizia; Galli, Letizia; Mautone, Daniele; Frusca, Tiziana (Acta Biomedica Atenei Parmensis, 2015)
In this paper we summarize our experience in diagnosis and treatment of 402 retrospectively collected tubal EP and review the most recent topics from the literature. Systemic Methotrexate (MTX) was effective in 56 out of 65 patients (failure rate 13.8%), in whom hCG level was significantly lower when compared to the failure group (p<0,05); we performed 299 salpingectomies, 297 of whom through laparoscopic approach. MTX single-dose is safe and effective in eligible patients; surgery represents the treatment of most of the EPs, mainly through laparoscopic approach.